Da’wah as an Alternative Approach in Covid-19 Health Protocol Campaign - Mochammad Irfan Achfandhy (Islam Realitas: Journal of Islamic and Social Studies, 2021)
This research aims to elaborate the communication strategy of Islamic Religious Counselors because communication strategies are an important aspect in the process of effectively transferring messages to the audiences. Islamic Religious Counselors are civil servant preachers who carry the mandate from the government to campaign for the Covid-19 health protocols through the da’wah (Islamic communication/propagation) approach. Da’wah and health materials are two different materials that pose challenges for Islamic Religious Counselors, especially in the communication patterns used. The research method used qualitative approach and multi-track communication theory by Thomas Tufte and Paolo Mefalopulos. Data were collected through structured interviews with six informants of Islamic Religious Counselor in Kalasan District and non-participant observations on each of their da’wah activities. The results showed that the preaching activities include recitation, socialization, social service and building relationships carried out with a multi-track communication strategy through a combination of a dialogic and one-step flow communication. Da’wah through a multi-track communication strategy has an impact on the affective side of religious congregations including attitudes, knowledge and awareness. Actualization of Islamic Religious Counselor is a viable alternative approach of the government and community in dealing with the Covid-19 pandemic.Penyuluh Agama Islam adalah pendakwah aparatur sipil negara yang mengemban amanah dari pemerintah untuk dapat mengampanyekan protokol kesehatan Covid-19 melalui pendekatan dakwah. Materi dakwah dan kesehatan merupakan dua materi berbeda yang menimbulkan tantangan bagi Penyuluh Agama Islam khususnya dalam pola komunikasi yang digunakan. Penelitian ini bertujuan untuk mengelaborasi strategi komunikasi Penyuluh Agama Islam karena strategi komunikasi merupakan aspek penting dalam proses transfer pesan kepada khalayak secara efektif.  Metode penelitian menggunakan pendekatan kualitatif dan menggunakan teori komunikasi multi-track dari Thomas Tufte dan Paolo Mefalopulos. Data dikumpulkan melalui wawancara terstruktur dengan informan berjumlah 6 orang Penyuluh Agama Islam di Kecamatan Kalasan dan observasi non-partisipan pada setiap kegiatan dakwah. Hasil penelitian menunjukkan bahwa aktivitas dakwah Penyuluh Agama Islam meliputi pengajian, sosialisasi, bakti sosial dan membangun relasi dilakukan dengan strategi komunikasi multi-track melalui kombinasi pendekatan komunikasi dialogis dan pendekatan satu arah. Dakwah melalui strategi komunikasi multi-track berdampak pada sisi afektif jama’ah meliputi sikap, pengetahuan dan kesadaran. Aktualisasi Penyuluh Agama Islam memberikan sebuah kontribusi sebagai alternatif pendekatan pemerintah maupun komunitas dalam menangani bencana Covid-19.